2016
DOI: 10.1111/aec.12383
|View full text |Cite
|
Sign up to set email alerts
|

Invasion, alien control and restoration: Legacy effects linked to folivorous insects and phylopathogenic fungi

Abstract: Invasive alien trees increase native tree stress and may increase attack by herbivores and pathogenic fungi. Alien tree removal should ameliorate such impacts. Here we compared levels of damage by phylopathogenic fungi and folivorous insects on Brabejum stellatifolium and Metrosideros angustifolia (native trees) and Acacia mearnsii (invasive tree species) among near pristine, invaded and restored sites. Generally, foliar damage levels were higher at invaded than at near pristine sites. Damage levels at restore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…Van der Colff et al (2015) found a different trend of arthropod community composition between native and invaded areas by A. mearnsii; arthropods could be using exotic trees as a pathway to reach isolated habitats. In this sense, leaf N content is an important driver of arthropod population dynamics in A. mearnsii stands (Maoela et al 2016a). Nevertheless, arthropod assemblages in the native community can be progressively recovered after the removal of the exotic (Maoela et al 2016b).…”
Section: Macrofaunamentioning
confidence: 99%
“…Van der Colff et al (2015) found a different trend of arthropod community composition between native and invaded areas by A. mearnsii; arthropods could be using exotic trees as a pathway to reach isolated habitats. In this sense, leaf N content is an important driver of arthropod population dynamics in A. mearnsii stands (Maoela et al 2016a). Nevertheless, arthropod assemblages in the native community can be progressively recovered after the removal of the exotic (Maoela et al 2016b).…”
Section: Macrofaunamentioning
confidence: 99%
“…In contrast, a management technique that both removes an invasive legume and reduces the abundance of compatible rhizobia in the soil could reduce the potential for reinvasion and future investment in control. Here, we extend beyond most studies of restoration efforts, which focus primarily on the aboveground effects of invasive species removal (Richardson et al ; Mason & French ; Konlechner et al ; Maoela et al ), to also examine belowground effects of invasion and removal of an invasive shrub.…”
Section: Introductionmentioning
confidence: 99%
“…Recovery of other taxa is less well quantified, largely because of the untested assumption that the recovery of native vegetation will facilitate the recovery of other taxa and subsequently ecosystem services and functions (Kaiser-Bunbury et al 2017). Recent South African studies do indicate spontaneous recovery of other taxa and a link to ecosystem services (Mgobozi et al 2008;Colvin et al 2009;Magoba and Samways 2010;Samways et al 2011;Maoela et al 2016;Modiba et al 2017). Invasive alien plant species were found to negatively impact most on seed dispersers and nectar-feeding bird pollinators (Mangachena and Geerts 2017).…”
Section: Costs and Benefits Of Restoration Projectsmentioning
confidence: 98%
“…Acacias shade out native species quicker than do pines. Their legacy effects include large soil-stored seed banks, increased leaf litter and biomass accumulation, increased pressure from folivorous insects and phylopathogenic fungi and changes to soil chemistry (Maoela et al 2016;Nsikani et al 2017;Strydom et al 2012;Yelenik et al 2004), thus altering ecosystem functions such as nutrient-cycling. Their rapid growth to canopy closure halts native seed set, resulting in depletion of native seed banks (Holmes 2002;Mostert et al 2017).…”
Section: Legacy Effects Ecosystem Functions and Driversmentioning
confidence: 99%